Necesidad de regular en el art. 188 del código del trabajo, en relación a establecer mayor indemnización por despido intempestivo a la mujer embarazada y después del parto - Sandoval Moreno, Marcelo Patricio (2014)
The Art. 153 of the Code of Labour expressed that "it can not terminate the contract of employment because of pregnancy of women workers and the employer can not be definitively replaced within the twelve week period set by the previous article. During this time the woman is entitled to full compensation, except for the provisions of the Social Security Act, as long as it covers or above the protections provided for in this Code." According to this provision prohibits the unfair dismissal by the unilateral termination of the employment contract to the pregnant and postpartum woman then up to twelve weeks, whereby a food and livelihoods of women and their families is assured, but if not stated in the legislation, which is the financial penalty or compensation payable by the employer for having dabbled in this prohibition. For in this case should be subject to the provisions of Art. 188 of the Labour Code, and the amount of compensation which marks the Labour Code for unfair dismissal is up to three years of service, with the value of three months' compensation over three years with the equivalent value of one month's pay for each year of service, but in no case exceed the value of twenty-five months of pay. Which I think that compensation is insufficient so a month per year of service does not solve the household economy of working, causing inequality in socioeconomic development of the working family. But if the compensation is greater economic incentive leads to the working by the effort to work, because the output was not due to the will of the working but a unilateral will of the employer, without any reason or cause to proceed his dismissal, and there is still a legal prohibition of the employer terminate the employment relationship.